ACTUAL ISSUES OF BUILDING SECURE COMMUNICATION CHANNEL CONSIDERING MODERN TECHNOLOGICAL CHALLENGES (Globalization and Business, 2023)
In today’s globalized, dynamic world, organizations’ dependence on information and, consequently, theirinterest and demands for information are growing. Information technologies play a crucial role in effective functioning andcontrol for modern companies and businesses. In the conditions of operational accessibility of necessary information it is possibleto adequate evaluation of current situation and to make timely decisions. At the same time, information must be available onlyto those to whom it is intended and unavailable - to all remaining. Computers are integrated into a common network forfast data transfer and efficient interaction. This connection must be reliable and secure. Modern companies are interestedin the possibility of using Internet channels. However, the principles of the building of the Internet give the chance to malefactors tosteal and distort information purposely. Corporate and broadcasting networks which are based on TCP/IP protocols and areconstructed on standard Internet applications (E-mail, Web, FTP) have no warranty from the invasion of unauthorized persons.In the article, the technology of creation of the virtual private networks (VPN), which is one of the optimal variants for the creation ofsecure channels of communication, is considered.